Consumer social network brand identification and personal branding. How do social network users choose among brand sites? - Wioleta Kucharska (Gdańsk University of Technology, Faculty of Management and Economics, 2016)
Social network brand sites are increasingly attracting the attention of scientists and managers intrigued by their potential application for brand value creation. The aim of this research is to fill the gap in understanding how users choose among social networking sites as an act of brand identification. Social network users, unlike it is in real life, do not need to own branded products to use their image. For this reason their identification with brands can bring interesting implications for those who study brand value creation. The study presents a new model whose structure of social network brand sites identification drivers varies for customer brand identification in the real and virtual worlds. The presented model reveals that personal branding is a planned effect of brand identification and is crucial for brand value creation in social networks.
Keywords: M30; M31; Y1; 330; CBI; social network; personal branding; brand loyalty